Analisis financiero a los balances del gobierno autónomo descentralizado parroquial de Chicaña, del cantón Yantzaza; durante el periodo 2014-2015 - Nugra Tibillin, Gladys Johana (2017)
The economy in our country presents important challenges and opportunities, even more within the public sector, when it comes to analyzing financial information, which allows us to measure compliance with the proposed goals. The Financial Analysis was carried out based on the general objective of carrying out the financial analysis on the balance sheets of the Decentralized Autonomous Government of Chicaña. Starting with a comparative analysis of each of the accounts of the Statement of Financial Position and the Income Statement, the own indicators for public sector institutions were applied; With these results a report on the Financial Analysis was executed, which is directed to the executives of the Entity, which will help to make future decisions Once the review of the Assets, Liabilities, Equity and Revenue and Expenses accounts has been completed, it can be established that the institution is solvent to cover its obligations either in the short or long term because its income is in the totality by transfers made Of the Central Government, does not generate income by self-management, its activities are handled by agreements between the Decentralized Provincial and Municipal Governments of the Province and Canton respectively. It is possible to establish that the Parochial Government maintains an acceptable solvency index and level of indebtedness its assets are not committed with third persons its liabilities are minimal in relation to the total of the resources, allowing it to fulfill its obligations and to maintain a good image of the institution.